Using Electronic Mail. . .now and if and when - James C. Webster (Journal of Applied Communications, 1983)
When Hal Taylor, Stan Prochaska and I had those extended conversations about moving the U.S. Department of Agriculture's news dissemination systems into the new world of computer electronics, never did I have the idea that I would soon become one of the early users.